Treating cancer stem cells and cancer metastasis using glucose-coated gold nanoparticles - Hu C (Dove Medical Press, 2015)
Chenxia Hu,1 Martin Niestroj,2,3 Daniel Yuan,4 Steven Chang,5 Jie Chen5,6 1Faculty of Chinese Pharmaceutical Science, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 2Canadian Light Source, Saskatoon, SK, Canada; 3Physics Department, Bonn University, Bonn, Germany; 4Biomedical Engineering Department, Johns Hopkins University, Baltimore, MD, USA; 5Faculty of Engineering, University of Alberta, Edmonton, AB, Canada; 6Canadian National Research Council/National Institute for Nanotechnology, Edmonton, AB, Canada Abstract: Cancer ranks among the leading causes of human mortality. Cancer becomes intractable when it spreads from the primary tumor site to various organs (such as bone, lung, liver, and then brain). Unlike solid tumor cells, cancer stem cells and metastatic cancer cells grow in a non-attached (suspension) form when moving from their source to other locations in the body. Due to the non-attached growth nature, metastasis is often first detected in the circulatory systems, for instance in a lymph node near the primary tumor. Cancer research over the past several decades has primarily focused on treating solid tumors, but targeted therapy to treat cancer stem cells and cancer metastasis has yet to be developed. Because cancers undergo faster metabolism and consume more glucose than normal cells, glucose was chosen in this study as a reagent to target cancer cells. In particular, by covalently binding gold nanoparticles (GNPs) with thio-PEG (polyethylene glycol) and thio-glucose, the resulting functionalized GNPs (Glu-GNPs) were created for targeted treatment of cancer metastasis and cancer stem cells. Suspension cancer cell THP-1 (human monocytic cell line derived from acute monocytic leukemia patients) was selected because it has properties similar to cancer stem cells and has been used as a metastatic cancer cell model for in vitro studies. To take advantage of cancer cells’ elevated glucose consumption over normal cells, different starvation periods were screened in order to achieve optimal treatment effects. Cancer cells were then fed using Glu-GNPs followed by X-ray irradiation treatment. For comparison, solid tumor MCF-7 cells (breast cancer cell line) were studied as well. Our irradiation experimental results show that Glu-GNPs are better irradiation sensitizers to treat THP-1 cells than MCF-7 cells, or Glu-GNPs enhance the cancer killing of THP-1 cells 20% more than X-ray irradiation alone and GNP treatment alone. This finding can help oncologists to design therapeutic strategies to target cancer stem cells and cancer metastasis. Keywords: glucose capped gold nanoparticles, cancer metastasis, cancer stem cells, irradiation therapy, targeted treatment, suspension cancer cells